COVID-19 and Co-production in Health and Social Care Research, Policy and Practice Volume 1 : The Challenges and Necessity of Co-production - Beresford, Peter; Farr, Michelle; Hickey, Gary; Kaur, Meerat; Ocloo, Josephine; Tembo, Doreen; Williams, Oli (Policy Press, 2021)
"EPDF and EPUB available Open Access under CC-BY-NC-ND licence. Groups most severely affected by COVID-19 have tended to be those marginalised before the pandemic and are now largely being ignored in developing responses to it. This two-volume set of Rapid Responses explores the urgent need to put co-production and participatory approaches at the heart of responses to the pandemic and demonstrates how policymakers, health and social care practitioners, patients, service users, carers and public contributors can make this happen. The first volume investigates how, at the outset of the pandemic, the limits of existing structures severely undermined the potential of co-production. It also gives voice to a diversity of marginalised communities to illustrate how they have been affected and to demonstrate why co-produced responses are so important both now during this pandemic and in the future."